1996
DOI: 10.2307/1131626
|View full text |Cite
|
Sign up to set email alerts
|

Relational Aggression, Overt Aggression, and Friendship

Abstract: This study (n = 315 9-12-year-olds) was conducted to assess whether the social problems that relationally and overtly aggressive children typically experience in the peer group context are also exhibited in the dyadic, friendship context. The qualities of children's friendships (e.g., levels of intimacy) and of the importance of those qualities (e.g., the importance of intimacy) were assessed with self-report instruments adapted from past research. Results indicated that the friendships of relationally aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
253
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(269 citation statements)
references
References 6 publications
13
253
3
Order By: Relevance
“…Intimacy is a key attribute in peer relationships that facilitates relationally aggressive acts. Indeed, relationally aggressive girls were more likely to report friend intimacy in their dyadic friendships than non-relationally aggressive girls (Grotpeter and Crick 1996). Taken together, these findings suggest that network features common among girls are likely to lead to increased levels of intimacy, and improved facilitation of relationally aggressive behaviors.…”
Section: The Effects Of ''Female'' Network Features On the Ratio Of Rmentioning
confidence: 81%
“…Intimacy is a key attribute in peer relationships that facilitates relationally aggressive acts. Indeed, relationally aggressive girls were more likely to report friend intimacy in their dyadic friendships than non-relationally aggressive girls (Grotpeter and Crick 1996). Taken together, these findings suggest that network features common among girls are likely to lead to increased levels of intimacy, and improved facilitation of relationally aggressive behaviors.…”
Section: The Effects Of ''Female'' Network Features On the Ratio Of Rmentioning
confidence: 81%
“…Another possibility is that such individuals maintain the approval of a few select friends by excluding from their peer group precisely those individuals from whom they fear negative evaluation. Interestingly, Grotpeter and Crick [1996] reported that relationally aggressive children tended to demand that their friends play only with them while excluding other classmates from their group. The authors suggested that by doing so, relationally aggressive children maintained control over select friendships.…”
Section: Discussionmentioning
confidence: 99%
“…The scale combined items from the Victimization of Self subscale of the Bully/Victim Questionnaire [38] Child Psychiatry Hum Dev (2007) 37:205-220 209 and the Social Experience Questionnaire -Self Report [46,47]. The Victimization of Self subscale has been shown in another study to correlate moderately with parentreported victimization of the child [35].…”
Section: Peer Victimizationmentioning
confidence: 99%